On the Yang - Mills Gravity - Tho, Nguyen Vien; Hoan, Nguyen Quoc (Communications in Physics, 2012)
The parallel between Yang-Mills theory and General Relativity isan attractive topic that motivated a lot of interestingresearches. Various versions of the gauge theory of gravity wereproposed which provided a deep understanding of such basisconcepts as the geometry of space-time, the connection betweensymmetry and dynamics. In this work we consider the problem ofinteraction between intrinsic degrees of freedom of particles withthe Lorentz gauge field solution that has the same singularfeature as for the Schwarzschild solution of General Relativity.The effective potential for a particle in the Schwarzschild-likeLorentz gauge field was investigated in comparison with Einsteinand Newtonian theories of gravity. The equations of motion forparticles allows planar motions that can be solved numerically. Wehave shown that there exit the Kepler-like orbits which correspondto certain sets of parameters and initial conditions. The obtainedresults can be regarded as an experimental evidence for theexistence of the "internal Lorentz symmetry" of point particlesthat is analogue to internal unitary symmetries